2019
DOI: 10.1038/s41598-019-47948-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling and antimicrobial resistance of Shiga toxin-producing Escherichia coli O26, O45, O103, O121, O145 and O157 isolates from cattle on cow-calf operations in South Africa

Abstract: In this study, 140 cattle STEC isolates belonging to serogroups O157, O26, O145, O121, O103 and O45 were characterized for 38 virulence-associated genes, antimicrobial resistance profiles and genotyped by PFGE. The majority of isolates carried both stx1 and stx 2 concurrently, stx2c , and stx2d ; plasmid-encoded genes ehxA, espP, subA and saa but lacked katP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 78 publications
1
15
1
Order By: Relevance
“…Interestingly, all of the isolates were harboring the eae gene, and it is reported that a significant majority of human STEC isolates obtained from HC or HUS patients contained eae [ 45 ]. The presence of subA in the E. coli strains was similar to that observed in some STEC strains isolated from human infections in the USA and Australia [ 46 ]. It was previously reported that the amount of stx2 production is capable of determining the severity of diseases caused by STEC strains.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, all of the isolates were harboring the eae gene, and it is reported that a significant majority of human STEC isolates obtained from HC or HUS patients contained eae [ 45 ]. The presence of subA in the E. coli strains was similar to that observed in some STEC strains isolated from human infections in the USA and Australia [ 46 ]. It was previously reported that the amount of stx2 production is capable of determining the severity of diseases caused by STEC strains.…”
Section: Discussionsupporting
confidence: 70%
“…Bouzari et al [ 55 ] reported a high prevalence of resistance against trimethoprim-sulfamethoxazole, tetracycline, and chloramphenicol in DEC strains isolated from Tehran, Iran, which is similar to the findings of this study. Several studies have documented the common occurrence of multidrug-resistant DEC pathotypes which could possibly be attributed to environmental acquisition of resistant genes, transmission of pathogens among humans of all age groups or by zoonosis [ 59 ], and occasionally as a result of indiscriminate use of different antibiotics in the management of infectious diarrhea [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…STEC may also harbor other important PAIs, including O-island (OI) 122, OI-43/48, and the high pathogenicity island. These encode many important non-LEE encoded (nle) effector genes as well as alternative virulence factors, including the toxin Sen (sen), adhesion factors (efa1, efa2, iha, aid-A1), and antimicrobial resistance genes (ureC, terC) (Schmidt and Hensel, 2004;Bugarel et al, 2010;Ju et al, 2013;Franz et al, 2015;Karama et al, 2019).…”
Section: Stec Pathogenic Factorsmentioning
confidence: 99%